Pembelajaran Menyenangkan sebagai Upaya Memberdayakan Potensi dan Menumbuhkan Minat Belajar Siswa SDIT Quratu A’yun Kota Gorontalo - Helena Badu; Magvirah El Walidayni Kau; Irmawaty Umar; Nurlaila Husain; Indri Wirahmi Bay; Sri Widyarti Ali; Fahria Malabar; Hendra Uloli (Universitas Negeri Gorontalo, 2023)
The purpose of this community service activity is to empower students’ potential in English through fun learning activities, as well as to foster students’ interest in learning English. This activity is conducted by implementing several games and songs in learning processes. The 5th grade students of SDIT Qurratu A’yun, which was located in Kota Tengah Districst, Gorontalo City, with a total number of 20 students were taken as the sample of this activity. This community service activity was carried out for eight meetings using various methods and materials that were considered fun for the students. The result showed that the students were interested and motivated in learning English that led to their vocabulary improvement.